Component of psychological training of basketball players at the stage of preliminary basic training in the preparatory period - Oksana Ivchenko; Olena Mitova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: determination and analysis of indicators of individual typological characteristics of the personality of basketball players 13-14 years old, and, taking them into account, provide recommendations for the training process on the basis of a differentiated approach. Material and methods: at the beginning of the reparatory period of 2019-2020 academic year the psychological diagnostics was carried out according to the method of G. Eysenck EPI (Eysenck Personality Inventory), with the help of which we obtained data on individual typological predominance of the type of temperament) indicators of basketball players at the stage of preliminary basic training. The study involved 30 basketball players 13-14 years old. Results:the issue of increasing the effectiveness of the organization of psychological training through the use of the opportunities for the development of the personality of athletes, its control and correction is one of the most important tasks facing both children and youth sports and sports of the highest achievements. Psychological preparation and control of the development of psychological readiness takes an important place in the educational and training process of basketball players, and the stage of preliminary basic training was no exception. Conclusions: the data obtained became the basis for recommendations for the correction of the educational and training process, namely: the distribution of basketball players by subgroups at the stage of preliminary basic training, taking into account the properties of the nervous system, individual typological characteristics, personality traits, sincerity according to the «scale of lies», which will increase the percentage of assimilation of educational material, to improve interpersonal relationships that develop between partners due to their compatibility, such as respect, mutual understanding, cohesion, interpersonal attraction, positive emotions, etc.